Pencapaian Identitas Politik Perempuan di Indonesia - Rizky Bangun Wibisono (Jurnal Mengkaji Indonesia, 2022)
Abstract: Efforts to break the patriarchy must be done by breaking down the political system that works in it. The issue of politics and women in an effort to achieve women's identity as a political being, an identity that is naturally owned by women but is not owned or recognized by them. Political issues are not only about the right to vote or the existence of women in the legislature but also drag on the private space and identity of women and their citizenship status. One of the efforts to achieve women's political identity is to provide space for women's representation in parliament. The presence of women is expected to be able to bring the interests of women in the nation and state. Therefore, a proposal for the RUU KKG emerged which was considered a proposal that actually came from women and would later be used for the benefit of women. However, along the way, efforts to achieve identity through the RUU KKG have not been able to show results due to the weak representation of women in the DPR and the mechanism of political party representation. Purpose: This article attempts to review efforts to form the RUU KKG. Design/Methodology/Approach: This article uses qualitative research methods. Findings: This article finds that the achievement of women's political identity cannot be achieved through struggles in parliament and will be more effective when giving more portions to extra-parliamentary institutions. Originality/Value: The novelty of this article is the author's attempt to explain the process of forming the RUU KKG from the point of view of political identity.